2018
DOI: 10.3389/fnins.2018.00012
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Intracellular ATP Generation and Tight Junction Protein Expression during the Course of Brain Edema Induced by Subacute Poisoning of 1,2-Dichloroethane

Abstract: The aim of this study was to explore changes in intracellular ATP generation and tight junction protein expression during the course of brain edema induced by subacute poisoning of 1,2-dichloroethane (1,2-DCE). Mice were exposed to 1.2 g/m3 1,2-DCE for 3.5 h per day for 1, 2, or 3 days, namely group A, B, and C. Na+-K+-ATPase and Ca2+-ATPase activity, ATP and lactic acid content, intracellular free Ca2+ concentration and ZO-1 and occludin expression in the brain were measured. Results of present study disclose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…Moreover, combined with the changes of tight junction proteins in the intervention groups, it has been proposed that ROS and reactive metabolites generated in the CYP2E1-mediated metabolism of 1,2-DCE might be involved in the disruption of tight junction proteins. In our previous study, it was reported that the expression levels of both ZO-1 and occludin decreased markedly at the early phase of brain edema, induced by subacute poisoning with 1,2-DCE ( Wang et al, 2018 ), consistent with present findings. In the current study, for the first time, we report the changes of claudin-5 expression in the brains of 1,2-DCE-poisoned mice and the association between the metabolism of 1,2-DCE and the disruption of tight junction proteins in the BBB.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, combined with the changes of tight junction proteins in the intervention groups, it has been proposed that ROS and reactive metabolites generated in the CYP2E1-mediated metabolism of 1,2-DCE might be involved in the disruption of tight junction proteins. In our previous study, it was reported that the expression levels of both ZO-1 and occludin decreased markedly at the early phase of brain edema, induced by subacute poisoning with 1,2-DCE ( Wang et al, 2018 ), consistent with present findings. In the current study, for the first time, we report the changes of claudin-5 expression in the brains of 1,2-DCE-poisoned mice and the association between the metabolism of 1,2-DCE and the disruption of tight junction proteins in the BBB.…”
Section: Discussionsupporting
confidence: 93%
“…This analysis revealed structural defects of mitochondria (cristae, matrix, and envelope) together with proliferation of their contacts with the ER. We can hypothesize that these alterations should significantly disturb the energy-dependent metabolism of cells and the balance of Ca 2+ between mitochondria and the cytoplasm as demonstrated in other studies on HD [ 28 , 57 ]. The uncovered accumulation of early and late autolysosomes in mutant cells together with artificial vacuolization of large organelles and disruption of integrity of their limiting membrane in 6H mutant cells strongly correlate with the point of involvement of the HTT protein in stimulation of autophagy in the early period and dysregulation of this process at later stages.…”
Section: Resultsmentioning
confidence: 65%
“…The hippocampus is a major target of estrogens in the brain due its high density of estrogen receptors which have the capacity to influence hippocampal volume through multiple actions, including altered gene expression, differential methylation of estrogen-responsive genes or by rapid-non genomic signaling pathways (Duarte-Guterman et al, 2015; Guintivano et al, 2014; Sárvári et al, 2015; Soma et al, 2018). Our results reveal an enrichment of estradiol’s effect on ‘neurogenic regions’ of the hippocampus, namely the granule cell layer and molecular layer of the dentate gyrus.…”
Section: Discussionmentioning
confidence: 99%